Transformation of Intangible Cultural Heritage in the Kenyan Coastal Region: Traditional Healing, Witchcraft and Witch Hunts in a Contemporary Context - Lukaszewicz, Aleksandra (Roczniki Kulturoznawcze, 2023)
The intangible heritage of Coastal Kenya pertains in great part to the Mijikenda people and consists of ceremonies, rituals, beliefs, forms of healing, prayer, and adjudication of disputes, which are subject to various cultural and religious factors that affect their perception and transform them. The younger generation’s perception of them, influenced by modern life’s technologized approach to culture, hugely contributes to such transformations. As a result, cultural roots fall into oblivion, which sometimes has dramatic effects, for example, the abandonment of witch hutching, paradoxically causing negative social effects. Not following traditional practices is not equal to disbelief in witches. Therefore, it often occurs that someone is accused of witchcraft to kill them without any possibility of reconciliation with the community, because the rejection of traditional practices causes the lack of any remediation for an instance of witchcraft, and elicits the easiest solution: the death of the accused. Such events happen to be combined with economic reasons, like the desire of some members of the youngest generation to sell the family land or even the sacred forest, in the care of the elders, who are then usually the ones accused as witches. This kind of cultural knot, appearing in the last 150 years due to interference of various cultures and religions, especially Christianity, requires careful consideration, also given the importance of interfaith dialogue, supported by the Coast Interfaith Council of Clerics Trust (CICC), among others. This investigation on transformation of cultural practices in Coastal Kenya is based on in-depth interviews with representatives of Malidni District Cultural Association (MADCA), field research and conversations with elders, and a review of research materials provided by the National Museums of Kenya Library in Malindi, and the Pwani University Library in Kilifi, Kenya.